MBO in the Curriculum Development Division, Bureau of Secondary Education, MEC a validation - Yamzon, Alice C. 1931- (1978)
Educational researchers, teaching aids specialists, statisticians, translators and statistical aides answered the Awareness and/or Knowledge Test, the Perception Survey (Phase II), and Output Analysis. Substantial evidence was gathered validating the effectiveness of the MBO managerial approach. A high level of consistency among the test results were obtained for all three research tools which measured the change from the pre- to the post-MBO periods.
Mimeographed.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Vita.
Keywords: Management by objectives; Curriculum planning